1996
DOI: 10.1080/02786829608965347
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Comparison of Four Differential Mobility Analyzers for Nanometer Aerosol Measurements

Abstract: The performance of four differential mobility analyzers (DMAs), namely the TSI-long, the TSI-short, the Hauke 31150, and the Spectromktre de Mobilite Electriqut Circulaire (SMEC) were evaluated under the same conditions of flow rates, flow ratio, input monodisperse aerosols, and transport-line lengths. The evaluations were performed under the conditions of 10 Ilmin sheath air and 1 llmin aerosol flow rates, and at a flow ratio of 10: 1. Monodisperse aerosols in the size range of 6 nm to 50 nm were obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 9 publications
2
61
0
Order By: Relevance
“…His analysis showed that the classical triangular transfer function is distorted into a broadened, continuous function by particle diffusion. Other investigators have also recognized the importance of diffusional broadening of the DMA transfer function, and applied inversions with broadened triangular distributions (Fissan et al 1996), with Figure 1. DMA transfer functions calculated using the expressions derived by Stolzenburg (1988).…”
Section: Inversion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…His analysis showed that the classical triangular transfer function is distorted into a broadened, continuous function by particle diffusion. Other investigators have also recognized the importance of diffusional broadening of the DMA transfer function, and applied inversions with broadened triangular distributions (Fissan et al 1996), with Figure 1. DMA transfer functions calculated using the expressions derived by Stolzenburg (1988).…”
Section: Inversion Methodsmentioning
confidence: 99%
“…Stolzenburg (1988) derived a semianalytical expression for the distorted transfer function over a decade ago, but only recently has use of this, or other similar representations, become routine (Zhang and Flagan 1996;Fissan et al 1996;Rossell-Llompart et al 1996). Convolution of a diffusionally broadened transfer function with the delay time distribution, while feasible, would be mathematically complex and computationally intensive.…”
Section: Introductionmentioning
confidence: 99%
“…A portable and cheap SMPS with high-resolution suitable for the needs of atmospheric monitoring and occupational hygiene is required. One of the most important developments of a portable SMPS is to design a small differential mobility analyzer (DMA), which are mainly three types of DMA including radial (Hurd and Mullins, 1962;Zhang et al, 1995;Fissan et al, 1996;Qi et al, 2008;Brunelli et al, 2009), cylindrical (Babis et al, 2009He, 2014) and planar (Erikson, 1921;Knutson and Whitby, 1975;Spangler, 2000;Zimmermann et al, 2007Zimmermann et al, , 2008. The various manufacturers of commercial DMAs utilize similar dimensions (Steer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tandem DMA (TDMA) technique, in which two DMAs are operated in series, was applied in the performance evaluation (Rader and McMurry 1986;Fissan et al 1996;Hummes et al 1996;Chen et al 2007). One of two calibrated DMAs (TSI Model 3081 and 3085) was used as the 1st DMA to classify monodisperse NaCl particles in selected sizes.…”
Section: Methodsmentioning
confidence: 99%